2005
DOI: 10.1111/j.1525-139x.2005.18318.x
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint: How Do Calcimimetics Fit Into the Management of Parathyroid Hormone, Calcium, and Phosphate Disturbances in Dialysis Patients?

Abstract: As suggested by its American brand name (Sensipar), the calcimimetic cinacalcet sensitizes the parathyroid cells to the extracellular calcium signal, suppressing parathyroid hormone (PTH) release and synthesis and preventing parathyroid cell proliferation. This primary PTH suppression decreases the release of calcium and phosphate from bone without increasing intestinal absorption of calcium and phosphate. Therefore cinacalcet decreases the risk of hypercalcemia and hyperphosphatemia in contrast to 1alpha-OH v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…Calcium-based phosphate binder use and the average dose increased in our study, but serum Ca decreased, consistent with a previous observation [9]. In the phase III cinacalcet trials, more patients on cinacalcet were started on calcium-based binders, but their mean dose was unchanged [5,6,7].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Calcium-based phosphate binder use and the average dose increased in our study, but serum Ca decreased, consistent with a previous observation [9]. In the phase III cinacalcet trials, more patients on cinacalcet were started on calcium-based binders, but their mean dose was unchanged [5,6,7].…”
Section: Discussionsupporting
confidence: 80%
“…Some suggest instituting cinacalcet if iPTH remains between 300 and 800 pg/ml despite traditional therapy [9]. Combination therapy, from both a pathophysiological and clinical perspective, may be more advantageous, utilizing several different mechanisms in treating resistant disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] It has been suggested that a different target PTH range should be used in patients with versus those without significant aluminum deposition in the bone. [37] Data from patients without evidence of aluminum intoxication on bone biopsy were analyzed in a study in Toronto [20].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cinacalcet hydrochloride (cinacalcet) often concurrently lowers PTH, Ca, P, and CaϫP levels among dialysis patients with SHPT (11)(12)(13)(14). Its use can provide sustained control of key biochemical parameters in those receiving traditional treatments for SHPT as judged by the achievement of values within the target ranges recommended by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF-KDOQI TM ) (15).…”
mentioning
confidence: 99%